1991
DOI: 10.1016/0266-7681(91)90052-p
|View full text |Cite
|
Sign up to set email alerts
|

Dupuytren’s Contracture: The Long-Term Results after Day Surgery

Abstract: 220 operations in 211 hands in 160 consecutive patients suffering from Dupuytren's contracture were performed from 1976 through 1984 at the Kuopio University Central Hospital in Finland. 179 operations were carried out as day cases. The mean follow-up was 3.2 years. Sub-total fasciectomy resulted in good immediate and long-term improvement in 86% of patients. The recurrence rate was 27%. Surgical treatment of Dupuytren's contracture was well-suited to day surgery. A properly planned follow-up programme is sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Rates after partial fasciectomy varied from 24.1% to 71% [9,[15][16][17], whilst rates between 5% and 39.7% were reported after total fasciectomy [11,13,18,19]. However, the mean periods between partial aponeurectomy and review varied between 33 months and ten years [9,[15][16][17] and were longer than those reported for total aponeurectomy which varied between 3-6 months and 47 months [11,13,18,19]. This, of course, begs the question of whether or not recurrence rates for total aponeurectomy might have been higher if patients had been examined at a later time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rates after partial fasciectomy varied from 24.1% to 71% [9,[15][16][17], whilst rates between 5% and 39.7% were reported after total fasciectomy [11,13,18,19]. However, the mean periods between partial aponeurectomy and review varied between 33 months and ten years [9,[15][16][17] and were longer than those reported for total aponeurectomy which varied between 3-6 months and 47 months [11,13,18,19]. This, of course, begs the question of whether or not recurrence rates for total aponeurectomy might have been higher if patients had been examined at a later time.…”
Section: Discussionmentioning
confidence: 99%
“…The two largest studies on partial aponeurectomy were reported by GELDMACHER [14] (n=1565) and BRENNER [12] (n=383 patients). Other studies referred to in this meta-analysis involve patient numbers of between 58 and 129 [9,10,[15][16][17]. The mean period between operation and review varied from 33 months to 10 years [9,[15][16][17].…”
Section: Techniques and Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery has been regarded as the only effective form of management for DC. A common disadvantage of surgical treatments is the high rate of recurrence, which ranges from 27% to 66% [1][2][3][4][5][6][7][8][9] . Fortunately, recurrence after surgical excision can be reduced by replacing the overlying skin with a skin graft, a procedure was first suggested by Piulachs in 1952 10 .…”
Section: Introductionmentioning
confidence: 99%
“…That skin replacement reduces the risk of recurrence has become an well accepted concept 15,16 . Hueston has even suggested that the skin may be a mediating neurovascular organ; exerting some control on the disease process rather than simply being secondarily involved 8 . Similarly, Hoopes et al have reported differing enzymatic activity in the dermis overlying nodules and bands as compared to that overlying normal fascia 17 .…”
Section: Introductionmentioning
confidence: 99%